The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1101/706556
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulation of lipid saturation without sensing membrane fluidity

Abstract: 20Cells maintain membrane fluidity by regulating lipid saturation, but the molecular 21 mechanisms of this homeoviscous adaptation remain poorly understood. Here, we have 22 reconstituted the core machinery for sensing and regulating lipid saturation in baker's yeast 23 to directly characterize its response to defined membrane environments. Using spectroscopic 24 techniques and in vitro ubiquitylation, we uncover a unique sensitivity of the transcriptional 25 regulator Mga2 to the abundance, position, and c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Phospholipid asymmetry and FA tail saturation both reduce membrane permeability to water, small solutes, and/or oxygen [50][51][52][53], which might provide additional advantages in the wild. Budding yeast and S. pombe utilize specialized gene expression programs executed by the membrane-sensing transcription factor Mga2 [54] to sustain FA desaturation in low-oxygen conditions [25,55]. In the future, it will be of interest to assess the wiring of this network in S. japonicus, given a markedly distinct physiology of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipid asymmetry and FA tail saturation both reduce membrane permeability to water, small solutes, and/or oxygen [50][51][52][53], which might provide additional advantages in the wild. Budding yeast and S. pombe utilize specialized gene expression programs executed by the membrane-sensing transcription factor Mga2 [54] to sustain FA desaturation in low-oxygen conditions [25,55]. In the future, it will be of interest to assess the wiring of this network in S. japonicus, given a markedly distinct physiology of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…2) Mutagenesis of individual TMH residues (V543-F551) including three aromatic residues lining one side of the TMH – one of which being the best-crosslinking residue F544C - causes no relevant functional defects (Figure S3A). These findings are notable because aromatic residues have been implicated in lipid/membrane sensing in other systems (37, 45, 46). 3) Our crosslinking data provide no evidence for a rotational re-organization of the TMHs during lipid bilayer stress (Figure 3C,D, Figure S3C).…”
Section: Discussionmentioning
confidence: 90%
“…scored the oligomerization propensity of IRE1α in cells via bimolecular fluorescence complementation in palmitate-treated cells and suggested that the increased lipid saturation might induce a conformational switch in the TMH region, which relies on a tryptophan (W457) as putative sensing residue and a conserved leucine zipper motif (SxxLxxx) involving serine 450 (37, 44). Intriguingly, such a rotation-based mechanism of sensing would be reminiscent of the lipid saturation sensor Mga2 from baker’s yeast controlling the expression of the essential fatty acid desaturase-encoding gene OLE1 (45, 46).…”
Section: Discussionmentioning
confidence: 99%